Disruption of Host-Symbiont Associations for the Symbiotic Control and Management of Pentatomid Agricultural Pests—A Review - Gonella, Elena; Orrù, Bianca; Marasco, Ramona; Daffonchio, Daniele; Alma, Alberto (Frontiers in Microbiology, 2020)
The family Pentatomidae (Hemiptera: Heteroptera) includes several invasive stink bug species capable to attack a large number of wild and cultivated plants, causing several damages to different crops. Pentatomids rely on obligate symbiotic associations with bacteria of the family Enterobacteriaceae, mainly of the genus Pantoea. A distinctive trait of these associations is the transmission route: during oviposition, females smear egg masses with symbiont-containing secretions, which are ingested by newly hatched nymphs, allowing the symbiont to pass through their digestive tract and establish in the crypts of the posterior midgut. Preventing newborn from orally acquiring symbionts seriously affects their fitness and survival. This symbiont inheritance process can be manipulated to develop innovative pest control measures by sterilization of egg masses prior to nymph hatching. This review summarizes the recent knowledge advances concerning the gut primary symbionts of pentatomids, with a specific focus on the most troubling pest species for agriculture. Current understanding of host colonization dynamics in pentatomids is presented, as well as the phenotypic effects determined in different insect species by the alteration of vertical transmission. Details on the current knowledge on the whole bacterial communities accompanying primary symbionts are analyzed. The recent research exploiting the perturbation of symbiont acquisition by pentatomid nymphs is discussed, by considering published work on laboratory and field trials with several active substances. These translational strategies are presently regarded as promising for limiting the populations of many important pentatomid pests in a sustainable way.